Effect of nimbolide on rat spermatozoa under in-vitro condition: A study on sperm functional events and antioxidants during capacitation (Journal of Laboratory Animal Science, 2024)
However, little evidence has been documented to evaluate the clear specific effects of neem-active ingredients in a rat model.  This study aims to evaluate the in vitro effects of nimbolide (tetranortriterpenoids group, one of the main components of  neem leaves), particularly on sperm functional studies, and biochemical and molecular events during capacitation in a dose dependent manner. The results showed a dose- and time-dependent decrease in the functional consequence of capacitation  process i.e., motility score, percentage of motile spermatozoa, Sperm Motility Index (SMI) and levels of molecular events  in sperm followed by declined spontaneous acrosome reaction (AR), which subsequently leads to lesser binding of cauda  epididymal sperm to the Zona pellucida (ZP). Biochemical studies have shown that the activities of antioxidant enzymes  such as superoxide dismutase (SOD), catalase, Glutathione reductase (GR) and Glutathione peroxidase (GPx) decreased  significantly while the levels of Hydrogen peroxide (H2O2) generation and lipid peroxidation (LPO) increased significantly  in the treated groups indicating nimbolide-induced oxidative stress in rat epididymal sperm. This study confirmed that  nimbolide convincingly inhibited sperm motility in rats by blocking certain biochemical pathways, such as energy  utilization, and showed that sperm capacitation was associated with a reduction in AR, with changes in antioxidant enzymes  reflecting a reduction at the levels of molecular events. This will lead us to produce a special product as a source of a new  male contraceptive.
Keywords: Nimbolide; Spermatozoa; Motility; ATP content; Biochemical; AR and Rat